2014
DOI: 10.2169/internalmedicine.53.2158
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism Possibly due to Lymphocytic Hypophysitis in a Patient with Type 1 Diabetes

Abstract: Hypopituitarism often develops insidiously, and undiagnosed hypopituitarism can influence the glycemic profile of patients with type 1 diabetes. We herein report the case of a 49-year-old man with type 1 diabetes and Hashimoto's thyroiditis who experienced an unexplained improvement in his glycemic level and recurrent severe hypoglycemia, despite a reduction in the dose of insulin. Based on the patient's endocrinological findings, he was diagnosed with hypopituitarism possibly due to lymphocytic hypophysitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…The phenomenon was rarely reported thereafter. Several studies showed that panhypopituitarism due to pituitary hemorrhage/infarction (including Sheehan's syndrome) induced a remarkable reduction of insulin doses in patients with type 1 diabetes [3,4,13,14]. A complete amelioration of diabetes induced by adrenal insufficiency was reported in patients with type 2 diabetes [5], but it has never been reported in a patient with type 1 diabetes with decreased insulin secretory capacity to an insulindependent level as observed in our patient.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The phenomenon was rarely reported thereafter. Several studies showed that panhypopituitarism due to pituitary hemorrhage/infarction (including Sheehan's syndrome) induced a remarkable reduction of insulin doses in patients with type 1 diabetes [3,4,13,14]. A complete amelioration of diabetes induced by adrenal insufficiency was reported in patients with type 2 diabetes [5], but it has never been reported in a patient with type 1 diabetes with decreased insulin secretory capacity to an insulindependent level as observed in our patient.…”
Section: Discussioncontrasting
confidence: 53%
“…Glucocorticoids increase blood glucose levels by increasing hepatic gluconeogenesis and inhibiting the uptake and utilization of glucose in peripheral tissues. Glucocorticoid deficiency can lead to an amelioration of glycemic control and/or a reduction of the insulin dose in patients with diabetes [2][3][4][5], but it is unclear whether the hyperglycemia in type 1 diabetes could be ameliorated without insulin treatment when complicated with adrenal insufficiency. Here, we describe the case of a patient who latently developed type 1 diabetes with endogenous insulin deficiency concurrently with adrenal insufficiency due to autoimmune hypophysitis.…”
Section: Adrenocorticotropic Hormone (Acth)mentioning
confidence: 99%
“…Hence, our patient's findings corresponded to a suspected case of lymphocytic hypophysitis according to the relevant diagnostic criteria. [1]…”
Section: Discussionmentioning
confidence: 99%
“…Hypopituitarism is a rare condition that may present as recurrent severe hypoglycemia and can influence the glycemic profile of patients with type 1 diabetes. [1,2] However, hypopituitarism often develops insidiously, [1] the diagnosis of hypopituitarism still remained challenging and often delayed by several months. In the present case report, we aimed to demonstrate the uncommon association of hypoglycemia, hyponatremia, and gastrointestinal symptoms with hypopituitarism in a female patient with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Resonance Image (MRI) is characterized by symmetric enlargement of the pituitary stalk or pituitary gland, with a strong homogeneous gadolinium enhancement. The definitive diagnosis would be given by histopathology if available [8].…”
mentioning
confidence: 99%